2018
DOI: 10.32413/pjph.v8i2.136
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive Prevalence Rate, Unmet Need for Family Planning and Its Associated Factors Among Women of Reproductive Age Group

Abstract: Background: Family planning includes knowledge, services, attitude, policies and practices which enable individuals to decide whether they want to have child and allow them to avoid unwanted pregnancy. Pakistan with population of 195.390 million with estimated population growth rate as 1.89 is the sixth most populous country in the world. Our objectives were to assess the total demand of family planning, contraceptive prevalence rate, unmet need for family planning and factors associated with unmet need of fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…The overall prevalence of FP use among married women in Mara region was 62.02% and its trends of modern FP use was 47.8% in 2019 and 35.5% from January to March 2020. The current result is higher compared to prevalence of FP use reported in the study conducted in Ghana 21% (22), in 17 countries in Sub-Saharan Africa 17% (23), in rural Northeastern Nigeria 26% (24), in Kenya 54% Mochache et al (25), in Ghana and Ethiopia 34.3%, 31.7% respectively (26,27) in Pakistan 34% (28). However, the current study prevalence of FP use achieved is above the national target of 60% by 2020 (13).…”
Section: Discussionmentioning
confidence: 56%
“…The overall prevalence of FP use among married women in Mara region was 62.02% and its trends of modern FP use was 47.8% in 2019 and 35.5% from January to March 2020. The current result is higher compared to prevalence of FP use reported in the study conducted in Ghana 21% (22), in 17 countries in Sub-Saharan Africa 17% (23), in rural Northeastern Nigeria 26% (24), in Kenya 54% Mochache et al (25), in Ghana and Ethiopia 34.3%, 31.7% respectively (26,27) in Pakistan 34% (28). However, the current study prevalence of FP use achieved is above the national target of 60% by 2020 (13).…”
Section: Discussionmentioning
confidence: 56%
“…15 Pakistan is facing high unmet need for family planning among women of reproductive age group. 16 Pakistan is committed to improve contraceptive prevalence rate (CPR) so in a recent interventional study published in 2020, estimates made using Inverse probability weighting (IPW) showed that the contraceptive prevalence rate (CPR) was increased from 51% to 64%, while the modern contraceptive prevalence rate (mCPR) increased from 34% to 53%. 17 Pakistan is facing high burden of abortion as well and practices related to abortion are poor too.…”
Section: Introductionmentioning
confidence: 99%
“…There are cultural and social barriers and fear of side effects which prevent them to seek help for contraception. 10 The present study was done to assess the knowledge and practices of contraception in females with cardiac disease, so that these females can be counseled effectively for contraceptive use.…”
Section: Introductionmentioning
confidence: 99%